South African immigrants constructions of Māori-Pākehā relations in Aotearoa-New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Wheeler, Kylie (Massey University, 2021)
Discursive studies of Māori-Pākehā relations in New Zealand (NZ) have typically contemplated the everyday talk of Pākehā, although more recently, a small number of studies have considered the discourse of Māori in relation to racism. This investigation contemplates a unique perspective of bicultural interactions in New Zealand by examining the discourse of South African immigrants concerning Māori-Pākehā relationships. The data for this analysis was gathered as part of a larger research project at Massey University concerning immigration and settlement of South African immigrants to New Zealand. Semi-structured interviews were completed with 16 participants. Questions were raised regarding identity and belonging, displacement, prejudice, Māori-Pākehā relations, as well as te Tiriti o Waitangi and the data for this project was analysed by way of discourse analysis. Four core themes were identified: neoliberal aspirations, racism concealed under the guise of te Tiriti o Waitangi, naturalised whiteness, and cultural affiliation. This study contributes insight into Māori-Pākehā relations in Aotearoa-New Zealand from the unique perspective of South African immigrants. Moreover, this research uncovers some alternate and unique interpretations of Māori and Pākehā relationships, as well as several typical constructions that support the current literature. This will add to the rich array of literature regarding indigene-settler relations globally and within Aotearoa-New Zealand. This study is of value for educationalists, researchers, psychologists, and policy makers.
Keywords: 441013 Sociology of migration, ethnicity and multiculturalism